A survey of high-z galaxies: serra simulations. Issue 4 (10th May 2022) - Pallottini, A; Ferrara, A; Gallerani, S; Behrens, C; Kohandel, M; Carniani, S; Vallini, L; Salvadori, S; Gelli, V; Sommovigo, L; D'Odorico, V; Di Mascia, F; et al.
ABSTRACT: We introduce serra, a suite of zoom-in high-resolution ($1.2× 10^4 \, {\rm M}_{\odot }$, $\simeq 25\, {\rm {pc}}$ at z = 7.7) cosmological simulations including non-equilibrium chemistry and on-the-fly radiative transfer. The outputs are post-processed to derive galaxy ultraviolet (UV) + far-infrared (FIR) continuum and emission line properties. Results are compared with available multiwavelength data to constrain the physical properties [e.g. star formation rates (SFRs), stellar/gas/dust mass, metallicity] of high-redshift 6 ≲ z ≲ 15 galaxies. This flagship paper focuses on the z = 7.7 sub-sample, including 202 galaxies with stellar mass $10^7 \, {\rm M}_{\odot }\lesssim M_\star \lesssim 5× 10^{10}\, {\rm M}_{\odot }$, and specific star formation rate ranging from ${\rm sSFR} \sim 100\, {\rm Gyr}^{-1}$ in young, low-mass galaxies to $\sim 10\, {\rm Gyr}^{-1}$ for older, massive ones. At this redshift, serra galaxies are typically bursty, i.e. they are located above the Schmidt–Kennicutt relation by a factor $κ _s = 3.03^{+4.9}_{-1.8}$, consistent with recent findings for [O iii ] and [C ii ] emitters at high z . They also show relatively large InfraRed eXcess (IRX = L FIR / L UV ) values as a result of their compact/clumpy morphology effectively blocking the stellar UV luminosity. Note that this conclusion might be affected by insufficient spatial resolution at the molecular cloud level. We confirm that early galaxies lie on the standard [C ii ]$\!-\!\rm SFR$ relation; their observed L [OIII] / L [CII] ≃ 1–10 ratios can be reproduced by a part of the serra galaxies without the need of a top-heavy initial mass function and/or anomalous C/O abundances. [O i ] line intensities are similar to local ones, making ALMA high- z detections challenging but feasible ($\sim 6\, \rm h$ for an SFR of $50\, \, {\rm M}_{\odot }\, {\rm yr}^{-1}$ ).